Application of Centrality Measures in Determining Regional Development Priorities in the Graph Representation of Kalimantan Island - Suyudi, Mochamad; Adli, Fajrul Iqbal; Supriatna, Asep Kuswandi (International Journal of Global Operations Research, 2022)
The relocation of the capital of the Republic of Indonesia to the Kalimantan raises new problems in regional development. In this paper the priority areas to be developed on the Kalimantan will be determined using Centrality Measures. The type of centrality measures used are degree centrality, leverage centrality, closseneess centrality, Jordan centrality, and betwenness centrality. The results show that Banjar, Ketapang, Sintang, KutaiÂ  Kertanegara, and Murung Raya areas are the areas that are central to the island of Kalimantan. Although the center of the island of Kalimantan, it is necessary to study the results of this paper with the actual distance of each region.